2010
DOI: 10.1161/circep.109.885095
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Arrhythmogenic Foci Associated With the Development of Perpetuation of Atrial Fibrillation

Abstract: Background-The presence of multiple arrhythmogenic sources may be associated with the perpetuation of atrial fibrillation (AF). In this study, we investigated the hypothesis that multiple foci might be involved in the development of AF persistency. Methods and Results-Two hundred fourteen consecutive patients with AF undergoing catheter ablation were enrolled in this study. The location of the arrhythmogenic foci was determined using simultaneous recordings from multipolar catheters before and after pulmonary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 44 publications
1
24
0
1
Order By: Relevance
“…[27][28][29][30] Non-PV triggers by themselves are known strong predictors of ATa recurrences: many studies have shown that their presence in the index procedure is associated with long-term AF recurrence, even in patients with PAF. [31][32][33] 15…”
Section: Predictors Of Atrial Tachyarrhythmias Recurrencementioning
confidence: 99%
“…[27][28][29][30] Non-PV triggers by themselves are known strong predictors of ATa recurrences: many studies have shown that their presence in the index procedure is associated with long-term AF recurrence, even in patients with PAF. [31][32][33] 15…”
Section: Predictors Of Atrial Tachyarrhythmias Recurrencementioning
confidence: 99%
“…We previously reported that multiple triggers were likely to be involved in the development of AF persistence. 9 In addition to the multiplicity of the AF triggers, the activity of the AF triggers might also have a great impact on the persistence.…”
Section: Ablation Of the Af Substrate In The Peaf Patientsmentioning
confidence: 99%
“…59,75 Current guidelines recommend consideration of more extensive ablation in this cohort in order to address a higher number of non-PV triggers. 76 However RCT data for this approach have been inconsistent (Table 3). …”
Section: Af Treatment Trials: Filling In the Gapsmentioning
confidence: 99%